Implementing Housing First Across Sites and Over Time: Later Fidelity and Implementation Evaluation of a Pan‐Canadian Multi‐site Housing First Program for Homeless People with Mental Illness. Issue 3 (13th March 2015) - Macnaughton, Eric; Stefancic, Ana; Nelson, Geoffrey; Caplan, Rachel; Townley, Greg; Aubry, Tim; McCullough, Scott; Patterson, Michelle; Stergiopoulos, Vicky; Vallée, Catherine; Tsemberis, Sam; Fleury, Marie-Josée; et al.
Abstract: This article examines later fidelity and implementation of a five‐site pan‐Canadian Housing First research demonstration project. The average fidelity score across five Housing First domains and 10 programs was high in the first year of operation (3.47/4) and higher in the third year of operation (3.62/4). Qualitative interviews (36 key informant interviews and 17 focus groups) revealed that staff expertise, partnerships with other services, and leadership facilitated implementation, while staff turnover, rehousing participants, participant isolation, and limited vocational/educational supports impeded implementation. The findings shed light on important implementation "drivers" at the staff, program, and community levels.